The ultrasonography evaluation of talar dysplasia as a potential prognostic factor for predicting the course and outcomes of clubfoot deformity treatment using Ponseti technique - Jiří Jochymek; Jakub Turek (Acta Orthopaedica et Traumatologica Turcica, 2018)
Objective: The aim of this study was to assess the role of sonographic evaluation of Talar dysplasia in predicting the outcome of standard Ponseti method in the treatment of clubfoot deformity. Methods: A total 23 children (15 boys and 8 girls; mean age: 18.2 ± 5.4 days (8–32)) who underwent Ponseti treatment were included in the study. Before the treatment, maximal talus length of affected and non-affected feet were measured by US and relative talar dysplasia ratio (RTDR) was calculated. The patients were categorized 2 groups according to RTDR: group A – mild and group B – severe deformity. Pirani score was used for clinical evaluation. The groups were compared in terms of number of the applied casts, need of percutaneous tenotomy of Achilles tendon (AchT) and frequency of deformity recurrence. Results: Pirani score was 4.46 for population (4.33 for group A; 4.54 for group B). Number of casts significantly differed between groups (p < 0.001) and positive correlation was found (r = 0.851, p < 0.001). AchT was performed in 56% cases for group A and in 86% cases for group B; no statistically significant difference was obtained (p = 0.162). Recurrence occurred in 2 patients belonging to group B without significant difference compared to group A (p = 0.502). Conclusion: Talar dysplasia assessment appeared as a promising prognostic factor for predicting the outcome of the Ponseti technique in treatment of clubfoot deformity. Level of evidence: Level IV, diagnostic study. Keywords: Ultrasonography, Clubfoot, Achilles tendon, Ponseti method, Tarsal bone, Talar dysplasia